The disproof and fall of the Riemann’s hypothesis by quadratic base: The correct variable distribution of prime numbers by the clear mathematics of the half-line values (“Chan function”) of prime numbers, “This paper has been withdrawn” - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
This paper has been withdrawn.